Ethnofederalism and Ethnic Voting - Richard Bluhm; Roland Hodler; Paul Schaudt (Center for Economic Studies and ifo Institute (CESifo), 2021)
We investigate how changes in the administrative-territorial structure affect ethnic voting. We present an event study design that exploits the 2010 constitutional reform in Kenya, which substantially increased the number of primary administrative regions. We find (i) strong evidence for a reduction in ethnic voting when administrative regions become less ethnically diverse and (ii) weak evidence for such a reduction when ethnic groups become less fragmented across regions. These results suggest that 'ethnofederal' reforms (leading to administrative borders that more closely follow ethnic boundaries) can mitigate ethnic politics in diverse countries.
Keywords: D02; D72; H77; J15; O55; 330; ethnofederalism; decentralization; territorial structure; ethnic divisions; ethnic voting; ethnic politics; Kenya